Context case Study of Live Communication Gamers on Facebook Gaming - Yakob, Freddy (MEDIASI Jurnal Kajian dan Terapan Media, Bahasa, Komunikasi, 2020)
This article discussed the development of technology information which has incorporated the most things in life, Internet technology is one of them. The Internet is recognized not only as channel for one-to-one communication, but also as one-to-many communication. Other than that, because of Internet technology, one can broadcast anything for everyone to watch. Facebook is one of the platform which become most popular social media who can broadcast videos by using feature â€œFacebook Gamingâ€ that will allow anyone to broadcast themselves while playing games. According to data showed in July 2019, Indonesia was the second largest country in watching live broadcast gamers online. Using qualitative approach and descriptive method, this article described about communication context carried out by these live gamers to their audience. Result showed live gamers not only doing mass communication, but also doing interpersonal communication context in which gave space between communicator and communicant that they are discussed things more than just about the games.